Masohi in the Christian and Islamic Villages of Siri Sori, Central Maluku, Post-Conflict - Johan Robert Saimima; Rouli Retta Trifena Sinaga; Islahuddin Islahuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article aims to explain the role of masohi in maintaining relations between the Christian and Muslim communities in the Christian and Islamic villages of Siri Sori, Central Maluku, that witnessed the communal religious conflict in the period of 1999-2004. Post-conflict social relation has the potential for establishing harmony, which is particularly important given the conflict’s tragic impact and complex social implications. This can be achieved through masohi, which embodies local wisdom. Masohi can contribute to peace and conflict resolution between the two communities. The research question in this study is whether masohi can adequately serve as a solution in that context. This research uses a qualitative approach using observation, literature study, and interviews with Christian and Muslim figures from the two communities who have practiced masohi in the Christian and Islamic villages of Siri Sori. All the data about masohi is collected, sorted, analyzed, and reconstructed using culturally-based historical awareness perspective. The results of this study show that: (1) masohi manifests in interfaith cooperation between the two communities in their history culture; (2) masohi has a constructive humanitarian characteristic; and (3) masohi can be preserved to ensure the welfare of the people and to preserve peace sustainably.